Pre Service English Teachers’ Strategies in Translating Spoof Texts - Eva Fitriani Syarifah (Universitas Majalengka, 2017)
AbstractIn recent year, Curriculum in Indonesia specifically in English curriculum, it has been influenced by Genre Based Approach. It can be seen from the content of English language textbook both in senior and junior high school which consist of texts from several of genre such as procedure, narrative, descriptive, discussion, news item, report, spoof, recount and others. In comprehending all of those types of text, the students need to understand the content of the text. However, in some parts of the text the students find that it is not easy to understand the meaning of some words. This situation happens because they have difficulties to process the words from the source language into their target language. Thus, this study tries to investigate pre service English teachers’ strategies in translating spoof texts. The data were obtained through observation and interview. The results show that there are some strategies used by pre service teachers in translating spoof text which include word for word translation, literal translation, adaptation, and free translation. It can be concluded that translation cannot be separated from English language teaching. Thus, it is important for the teachers need to comprehend strategies in translation. Keywords: Pre Service Teachers, Strategies in Translation, Spoof Text